2023
DOI: 10.3847/1538-4357/acda87
|View full text |Cite
|
Sign up to set email alerts
|

Solar Wind Modeling with the Alfvén Wave Solar atmosphere Model Driven by HMI-based Near-real-time Maps by the National Solar Observatory

Abstract: We explore the performance of the Alfvén Wave Solar atmosphere Model with near-real-time (NRT) synoptic maps of the photospheric vector magnetic field. These maps, produced by assimilating data from the Helioseismic Magnetic Imager (HMI) on board the Solar Dynamics Observatory, use a different method developed at the National Solar Observatory (NSO) to provide a near contemporaneous source of data to drive numerical models. Here, we apply these NSO-HMI-NRT maps to simulate three full Carrington rotations: 2107… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Jin et al (2022) assessed the influence of input magnetic maps on modeling the solar wind and concluded that it is important to consider the model uncertainty due to the imperfect magnetic field measurements. Sachdeva et al (2021Sachdeva et al ( , 2023 used AWSoM to simulate solar maximum conditions with different input magnetograms, and confirmed that the simulated solar wind at 1 au can be very different when different input magnetograms are used.…”
Section: Introductionmentioning
confidence: 75%
“…Jin et al (2022) assessed the influence of input magnetic maps on modeling the solar wind and concluded that it is important to consider the model uncertainty due to the imperfect magnetic field measurements. Sachdeva et al (2021Sachdeva et al ( , 2023 used AWSoM to simulate solar maximum conditions with different input magnetograms, and confirmed that the simulated solar wind at 1 au can be very different when different input magnetograms are used.…”
Section: Introductionmentioning
confidence: 75%
“…et al, 2021a, 2021bSachdeva et al, 2019). This effect becomes particularly pronounced during solar maxima, where the simulated results can vary with the specific input magnetograms utilized (Arge et al, 2024;Huang et al, 2024;Sachdeva et al, 2021Sachdeva et al, , 2023. Another factor could be the significant gradients in strong magnetic fields, which pose challenges for numerical methods in terms of convergence and non-physical deviations, complicating high-quality numerical simulations (Gressl et al, 2014).…”
Section: Experiments For Solar Maximummentioning
confidence: 99%